Glyburide attenuates B(a)p and LPS‐induced inflammation‐related lung tumorigenesis in mice. Issue 8 (26th May 2021) - Li, Mengyuan; Liu, Hong; Shao, Hua; Zhang, Peng; Gao, Min; Huang, Li; Shang, Pingping; Zhang, Qiao; Wang, Wei; Feng, Feifei
Abstract: Glyburide (Gly) could inhibit NLRP3 inflammasome, as well as could be treated with Type 2 diabetes as a common medication. Despite more and more studies show that Gly could influence cancer risk and tumor growth, it remains unclear about the effect of Gly in lung tumorigenesis. To evaluate whether Gly inhibited lung tumorigenesis and explore the possible mechanisms, a benzo(a)pyrene [B(a)p] plus lipopolysaccharide (LPS)‐induced non‐diabetes mice model was established with B(a)p for 4 weeks and once a week (1 mg/mouse), then instilled with LPS for 15 weeks and once every 3 weeks (2.5 μg/mouse) intratracheally. Subsequently, Gly was administered by gavage (10 μl/g body weight) 1 week before B(a)p were given to the mice until the animal model finished (when Gly was first given named Week 0). At the end of the experiment called Week 34, we analyzed the incidence, number and histopathology of lung tumors, and detected the expression of NLRP3, IL‐1β, and Cleaved‐IL‐1β protein. We found that vehicles and tricaprylin+Gly could not cause lung carcinogenesis in the whole process. While the incidence and mean tumor count of mice in B(a)P/LPS+Gly group were decreased compared with B(a)p/LPS group. Moreover, Gly could alleviate inflammatory changes and reduce pathological tumor nest numbers compared with mice administrated with B(a)p/LPS in histopathological examination. The B(a)p/LPS increased the expression of NLRP3, IL‐1β, and Cleaved‐IL‐1β protein significantly than Vehicle, whereas decreased in B(a)P/LPS+Gly (0.96 mg/kg) group compared with B(a)p/LPS group. Results suggested glyburide might inhibit NLRP3 inflammasome to attenuate inflammation‐related lung tumorigenesis caused by intratracheal instillation of B(a)p/LPS in non‐diabetes mice.